Learning for Adoption: Technology Adoption in Developing Country Agriculture - Janvry, A. de; Macours, K.; Sadoulet, E. (CGIAR Independent Science and Partnership Council, 2016)
Policy briefs from the workshop organized by Ferdi and SPIA on June 1 and 2, 2016, in Clermont-Ferrand.